Plug-and-play Physical Computing with Jacdac - Devine, James; Moskal, Michal; Halleux, Jonathan "Peli" de; Ball, Thomas; Hodges, Steve; D’Amone, Gabriele; Gakure, David; Finney, Joe; Underwood, Lorraine; Hartley, Kobi; Kos, Paul; Oppenheim, Matt (Proceedings of the ACM on Interactive, Mobile, Wearable and Ubiquitous Technologies, 2022)
Physical computing is becoming mainstream. More people than ever-from artists, makers and entrepreneurs to educators and students-are connecting microcontrollers with sensors and actuators to create new interactive devices. However, physical computing still presents many challenges and demands many skills, spanning electronics, low-level protocols, and software-road blocks that reduce participation. While USB has made connecting peripherals to a personal computing device (PC) trivial, USB components are expensive and require a PC to operate. This makes USB impractical for many physical computing scenarios where cost, size and low power operation are often important.